Into the night : tales of nocturnal wildlife expeditions - Adams, Rick A. (Rick Alan) (University Press of Colorado, 2013)
This collection of essays from professional scientists and naturalists provides an enlightening look at the lives of field biologists with a passion for the hidden world of nocturnal wildlife. This book explores the harrowing, fascinating, amusing, and largely unheard personal experiences of scientists willing to forsake the safety of daylight to document the natural history of these uniquely adapted animals. Contributors tell of confronting North American bears, cougars, and rattlesnakes; suffering red ctenid spider bites in the tropical rain forest; swimming through layers of feeding-frenzied hammerhead sharks in the Galapagos; evading the wrath of African bull elephants in South Africa; and delighting in the curious and gentle nature of foxes and unconditional acceptance by a family of owls. They describe "fire in the sky" across a treeless tundra, a sea ablaze with bioluminescent algae, nighttime earthquakes on the Pacific Rim, and hurricanes and erupting volcanoes on a Caribbean island. This book reveals rare and unexpected insights into nocturnal field research, illuminating experiences, discoveries, and challenges faced by intrepid biologists studying nature's nightly marvels across the globe. This volume will be of interest to scientists and general readers alike. --